Distribusi Pengiriman File Multimedia Secara RealTime dengan Jaringan WAN Frame Relay - Fransiscus Ati Halim (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2017)
Today's communications networks are built using high-speed digital trunks that inherently provide high throughput, minimal relay, and a very low error rate. Such transmission networks supply highly reliable service without the overhead of error control functions. Frame relay is a packet-mode transmission network service that exploits these network characteristics by minimizing the amount of error detection and recovery performed inside the network [1]. In addition, real time network based systems can also minimize the possibility of employees committing fraud resulting in losses for the company. The research was carried out in a service provider video ad impressions company, which has fifteen branches in the islands of Java and Sumatra. The problem is the revenue reporting is not real-time and non-standard video file format ads to each branch. This is because the distribution process with the hard disk media are still using courier services. Based on user demand, it was decided to use the computer network using Frame Relay technology. With the computer network that connects all the branches to the head office, the data updating process can be done in a shorter time than the previous system and will reduce fraud forms of each branch and enable the achievement of a better quality of service to customers. Index Terms—Computer Network, Frame Relay